Neural correlates of oral word reading, silent reading comprehension, and cognitive subcomponents. (May 2018) - Xia, Zhichao; Zhang, Linjun; Hoeft, Fumiko; Gu, Bin; Gong, Gaolang; Shu, Hua
The ability to read is essential for cognitive development. To deepen our understanding of reading acquisition, we explored the neuroanatomical correlates (cortical thickness; CT) of word-reading fluency and sentence comprehension efficiency in Chinese with a group of typically developing children ( N = 21; 12 females and 9 males; age range 10.7–12.3 years). Then, we investigated the relationship between the CT of reading-defined regions and the cognitive subcomponents of reading to determine whether our study lends support to the multi-component model. The results demonstrated that children's performance on oral word reading was positively correlated with CT in the left superior temporal gyrus (LSTG), left inferior temporal gyrus (LITG), left supramarginal gyrus (LSMG) and right superior temporal gyrus (RSTG). Moreover, CT in the LSTG, LSMG and LITG uniquely predicted children's phonetic representation, phonological awareness, and orthography–phonology mapping skills, respectively. By contrast, children's performance on sentence-reading comprehension was positively correlated with CT in the left parahippocampus (LPHP) and right calcarine fissure (RV1). As for the subcomponents of reading, CT in the LPHP was exclusively correlated with morphological awareness, whereas CT in the RV1 was correlated with orthography–semantic mapping. Taken together, these findings indicate that the reading network of typically developing children consists of multiple sub-divisions, thus providing neuroanatomical evidence in support of the multi-componential view of reading.